Current Application and Meta-analysis of Traditional Chinese Medicine emotional nursing for colorectal cancer patients' psycho-somatic rehabilitation after radical surgery (中医情志护理在结直肠癌根治术后患者心身康复中应用现状及Meta分析) - SUN Lingyun (孙凌云); PENG Rongyan (彭蓉晏); LIU Jiaxi (刘稼玺); YAN Yunzi (闫蕴孜); YANG Yufei (杨宇飞); ZHAO Nan (赵楠) (中西医结合护理)
Objective To systematically evaluate the efficacy and current application of emotional nursing of Traditional Chinese Medicine(TCM) in psycho-somatic rehabilitation for early-stage colorectal cancer(CRC) patients after radical surgery, so as to provide reference for clinical practice and future research. Methods CNKI, VIP, Wanfang, Embase, Pubmed, Conchrane database were retrieved, and the randomized controlled clinical trials of TCM emotional nursing on psychosomatic rehabilitation of early-stage colorectal cancer patients after radical surgery from 2010 to 2022 was collected. The literatures met the inclusion and exclusion criteria were selected for data extraction and quality evaluation. Meta-analysis was conducted through RevMan5. 3 statistical software. Results Totally 13 studies were included, and 1034 patients were enrolled. Meta-analysis results showed that TCM emotional nursing could significantly reduce the scores of Self-rating Anxiety Scale (SAS) ［MD=-3. 57, 95% CI: (-4. 02, -3. 12), P＜0. 01］and Self-rating Depression Scale (SDS)［MD=-6. 70, 95% CI: (-7. 28, -6. 11), P＜0. 01］ of patients after intervention compared with conventional nursing, and could improve the quality of life, sleep, pain of patients, and improve the compliance and satisfaction of nursing and cancer treatment. Conclusion TCM emotional nursing could promote the psychosomatic rehabilitation of early-stage colorectal cancer patients after radical surgery, but it still needs to further improve the quality of research, optimize and integrate the nursing practice process and details, and strive to obtain higher level of evidence, so as to better help patients benefit. (目的 系统评价中医情志护理在早中期结直肠癌根治术后患者心身康复中应用效果及现状, 为临床实践及后续研究开展提供依据。方法 检索CNKI、维普、万方、Embase、Pubmed、Conchrane, 收集2010年—2022年中医情志护理干预早中期结直肠癌术后患者心身康复的随机对照临床试验研究, 筛选符合纳入排除标准的文献进行资料提取和质量评价, 通过RevMan5. 3 统计软件进行Meta分析。结果 共纳入13项研究, 共计1034例患者。Meta分析结果显示, 中医情志护理相比常规护理能够显著降低干预后患者焦虑(SAS)［MD=-3. 57, 95% CI: (-4. 02, -3. 12), P＜0. 01］、抑郁(SDS)［MD=-6. 70, 95% CI: (-7. 28, -6. 11), P＜0. 01］评分, 并有可能改善患者生活质量、睡眠、疼痛, 并且提高护理及治疗依从性和满意度。结论 中医情志护理能够促进结直肠癌术后患者心身康复, 但仍需进一步提高研究质量、优化整合护理实践流程和细节, 争取获得更高级别循证医学证据, 从而更好地帮助患者获益。)